Penerapan Manajemen Konflik dalam Menangani Masalah Komunikasi Anak ABK (Tuna Rungu) dalam Pengelolaan Kafe Ksuli di Kabupaten Jember - Dwitama, Muhammad Wahyu Putra; Firdaus, Wildan; Kurniawan, Syafril Bagus; Fitriana, Ani Qotus Zuhro’ (Jurnal Ekonomi Manajemen dan Bisnis (JEMB), 2022)
This research aims to apply conflict management in addressing communication issues among deaf children in managing Kasuli Cafe in Jember Regency. Through data collection using interview and observation techniques, and data analysis conducted, several important findings can be concluded: Communication Issues of Deaf Children: Deaf children in Kasuli Cafe face challenges in communicating with clients and the surrounding environment. These challenges include difficulties in conveying messages, understanding customer requests, and interacting effectively. Application of Conflict Management: The application of conflict management in cafe management can help address communication issues among deaf children. Recommended steps include the use of audio and visual media, comprehensive instruction boards, communication training, and psychosocial support. Success of Existing Strategies: Kasuli Cafe has implemented several successful strategies in addressing communication issues among deaf children. Instruction using sign language, awareness of the needs of deaf children, and collaboration among cafe owners, deaf children, and clients contribute to improved interaction and communication. Implications of Research Findings: The findings of this research have important implications in the management of Kasuli Cafe and in a broader context. Specific recommendations for implementing conflict management, raising public awareness, and contributing to research and practice are important outcomes to consider. In conclusion, the application of conflict management in addressing communication issues among deaf children in managing Kasuli Cafe in Jember Regency plays a significant role. Through the recommended steps, it is expected that deaf children can communicate and interact more easily with clients, thus creating an inclusive environment that supports their development.